DAMPAK PENDIRIAN PT. BUMI MENTARI KARYA PADA PENDAPATAN USAHATANI KELAPA SAWIT MASYARAKAT DI DESA TUNGGANG KECAMATAN PONDOK SUGUH KABUPATEN MUKOMUKO - Supriyadi, Eeen; Nabiu, Musriyadi; Widiono, Septri (Jurnal AGRISEP, 2012)
The research was conducted in two places; in Tunggang village and Padang Gading Village subdistrict of Sungai Rumbai, Mukomuko District, Bengkulu Province on February 5 to March 5, 2011. These research areas were selected purposively. Tunggang village is just exactly the same as the plant location of PT Bumi Mentari Katya while Padang Gading Village, as comparison village. The objective of this research is to examine the impact of establishment of PT Bumi mentari Karya on farming income in the communities around the oil palm plant. In this study, the palm oil farmers which are being sampled are 69 people. On regard with it, this study only performs with and without analysis; the initial state of the palm oil farmers (before the company) is described qualitatively which is Padang Gading Village as the comparison village and the state of palm oil farmers after the company is established. Income farming Crude plam more the after PT. Bumi Mentari karya means were statistically difference These results indicate presence of the oil palm industry PT. Bumi Mentari Karya Giving a positive impact on farm income of oil palm Tunggang Village.